2021
DOI: 10.1371/journal.pone.0254141
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between socio-demographics, body composition, emotional state, and social support on metabolic syndrome risk among adults in rural Mongolia

Abstract: Background In Mongolia, where there is a large regional gap in the quality of healthcare services, metabolic syndrome (MetS) is steadily increasing. However, there are few studies on the risk level of MetS and affecting factors among adults living in rural Mongolia. This study aims to explore the relationship between socio-demographics, clinical characteristics, emotional state, and social support on the risk level of MetS prevalence among adults living in rural Mongolia. Methods In this cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In addition, our findings showed that the rate of MetS according to the NCEP ATP III was 43.5%, suggesting that the prevalence of MetS continues to increase in line with the dramatic rise in the prevalence of obesity. The observed prevalence is similar to that identified in studies of rural populations in Mongolia (Kim et al, 2021), Korea (Lee et al, 2018), and Poland (Czekajło et al, 2019). However, other studies in rural areas of China showed a prevalence of MetS ranging from 14.3% (Guo et al, 2017) to 24.2% (Ling et al, 2020), somewhat lower than in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, our findings showed that the rate of MetS according to the NCEP ATP III was 43.5%, suggesting that the prevalence of MetS continues to increase in line with the dramatic rise in the prevalence of obesity. The observed prevalence is similar to that identified in studies of rural populations in Mongolia (Kim et al, 2021), Korea (Lee et al, 2018), and Poland (Czekajło et al, 2019). However, other studies in rural areas of China showed a prevalence of MetS ranging from 14.3% (Guo et al, 2017) to 24.2% (Ling et al, 2020), somewhat lower than in this study.…”
Section: Discussionsupporting
confidence: 86%
“…A lack of social support and social disengagement or feelings of loneliness are closely linked to CVD, depression, dementia, disability, cognitive decline, and mortality (Mehrabi & Béland, 2020). Interestingly, a few recent studies evidence that environmental factors such as social support, loneliness, and social isolation may affect the prevalence of MetS (Badcock et al, 2019; Kim et al, 2021; Winterton et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Older adults are more vulnerable to poverty as most cannot work for pay and their pensions and benefits are insufficient to sustain a healthy livelihood and many lack essential information about potential resources they may need [ 18 ]. Loneliness, an inability to access social and health care, and depression are therefore common [ 19 ]. Owing to the wide geographic dispersal of the population and poor infrastructure in rural and outlying areas, older adults, including nomadic pastoralists, who live in these areas are likely to be especially disadvantaged.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have reported that MeS prevalence was related to demographic characteristics, including aging ( 41 44 ) (Hypothesis 1.2).…”
Section: Introductionmentioning
confidence: 99%